2011
DOI: 10.1631/jzus.b1000185
|View full text |Cite
|
Sign up to set email alerts
|

Current recognition and management of intra-abdominal hypertension and abdominal compartment syndrome among tertiary Chinese intensive care physicians

Abstract: This survey was designed to clarify the current understanding and clinical management of intra-abdominal hypertension (IAH)/abdominal compartment syndrome (ACS) among intensive care physicians in tertiary Chinese hospitals. A postal twenty-question questionnaire was sent to 141 physicians in different intensive care units (ICUs). A total of 108 (76.6%) questionnaires were returned. Among these, three quarters worked in combined medical-surgical ICUs and nearly 80% had primary training in internal or emergency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
2
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 22 publications
1
31
2
7
Order By: Relevance
“…(5,16) A second study revealed significantly higher mortality indices in critically ill patients presenting with increased IAP compared to unaffected patients (37.9% and 19.1% respectively). (8,16) These data suggest increased IAP is common among critically ill patients, and may increase morbidity and mortality risks.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(5,16) A second study revealed significantly higher mortality indices in critically ill patients presenting with increased IAP compared to unaffected patients (37.9% and 19.1% respectively). (8,16) These data suggest increased IAP is common among critically ill patients, and may increase morbidity and mortality risks.…”
Section: Discussionmentioning
confidence: 99%
“…(8,10,13,16,18,25,26) A prospective study involving 13 intensive care unit (ICUs) in Belgium, Austria, Israel, Brazil and Australia reported IAH and ACS prevalence of 32.1% and 4.2%, respectively, upon patient admission. (5,16) A second study revealed significantly higher mortality indices in critically ill patients presenting with increased IAP compared to unaffected patients (37.9% and 19.1% respectively). (8,16) These data suggest increased IAP is common among critically ill patients, and may increase morbidity and mortality risks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations